Types and Capacity of Coral Reefs Collecting as Material For Making Lime, In Gunung Malang Village, East Lombok - Dining Aidil Candri; Lia Mar’atus Sholeha; Hilman Ahyadi; Yuliadi Zamroni (Jurnal Biologi Tropis, 2022)
Coral reefs ae onne of the ecosystems who have both ecological and economical function. I Gunung Malang community, coral reef have been used as main mateerial in lime powder production. The aim of this research to identified the species, distribution and capacity of coral reefs in lime powder production and than how the marketing system of the product. This research conducted from January to September 2018. The data was collected by measurement and identificatio of coral ad then interviewed the lime powder labours. The result of the research reported 29 species of coral from 17 genera and 8 families which was taken in 9 locations, six of it are live coral reef sites and the other are dae coral sites. Acropora abrolhosensis is dominant species with 605 Kg of coral mininng, followed by acropora sp with 535 kg and acropora palifera with 307 kg. The capacity of coral used inn are processig of lime powder production between 2000-3000 Kg, it will product 60-100 sacks of lime powder with 25 to 30 Kg in each sack. The lime powder in not sale directly to the consumers by the producer but it saleing to mainn collectors and then distriuted to the consumers or building stores.